Study of Thermal and Optical Sensitivity of Higher Thermo luminescence Glow Peaks in Synthetic Quartz Material (International Journal of Innovative Research in Computer Science & Technology, 2022)
In the present scenario, 600 oC and 1000 oC  annealed synthetic quartz material were irradiated by beta  doses. The thermoluminescence glow curves are recorded for  treated sample under influence of optical bleaching  temperature and cutoff duration of 290 oC preheat  temperature. The thermal and optical sensitivity of higher  temperature TL glow peaks are to be examined including  their dose response. Under the influence of optical bleaching  either at room temperature or 160 oC, the growth of 375 oC  TL glow peak is observed at 600 oC annealed sample by  complete bleaching of 350 oC glow peak. However, the  thermal stability and optical sensitivity of this peak is  increased when the temperature is increased to1000 oC  annealed sample accordance with new 220 oC TL glow peak by complete optical bleaching of 300 oC glow peak. The  cutoff durations of 290 oC preheat temperature followed  optical bleaching at 160 oC show unique contribution of 375  oC and 220 oC glow peaks in 600 oC and 1000 oC annealed  sample respectively. This Study focussed on the Thermal and  Optical Sensitivity of Higher Thermo luminescence Glow  Peaks in Synthetic Quartz Material. The changes in TL  outcomes are elaborated by thermal and optical sensitization  properties of TL traps under annealing treatment, pre-heat  temperature and optical bleaching temperature.
Keywords: Annealing Treatment; Beta DosE; Optical Bleaching; Pre-Heat Duration; Synthetic Quartz; Thermo luminescence